The Impact of HST on European Astronomy - Macchetto, F. Duccio.; Macchetto, F. Duccio. (Astrophysics and Space Science Proceedings, 2010)
The Hubble Space Telescope has facilitated major contributions to a wide range of topics in astronomy: The study of nearby planets The processes of star and planet formation The stellar and interstellar components of galaxies The discovery that most, if not all, galactic nuclei harbor a massive black hole that profoundly affects their evolution The realisation that the universe as a whole is undergoing acceleration as a result of a yet unknown form of "dark energy". This volume offers a broad perspective of the advancements made possible by the HST over its almost two decades of operation and emphasises their impact on European astronomical research. These proceedings of 41st symposium in the ESLAB series of the European Space Agency collect the oral and poster papers that were presented and discussed during the meeting.